The Variability studies in Casuarina clones - Garg, Rakesh; Sra, Manpreet Singh; Avtar Singh; A. Nicodemus (Indian Journal of Agroforestry, 2023)
Estimates of phenotypic coefficient of variation, genotypic coefficient of variation and heritability reflected the predominance of heritable variation for most of the characters under study. Maximum PCV and GCV was recorded in branch thickness followed by tree stem volume and crown spread. Heritability was recorded maximum for branch thickness (91.57%) followed by tree height (65.62). Genetic gain was recorded maximum for branch thickness (67.04%) followed by tree stem volume (26.88%) and crown spread (21.99%). High significant phenotypic correlation was found for tree stem volume with diameter at breast height (0.9495). Path analysis demonstrated the direct and indirect effect of the traits on the performance of tree stem volume. The highest value was registered for diameter at breast height (0.7356) and the least direct effect was registered for crown spread (-0.0605) whereas the indirect effect was observed higher in crown spread for diameter (0.5647) and the least effect was registered by number of branches for tree height (-0.0833).